2018
DOI: 10.1159/000495849
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Pitfalls in the Assessment of Early Gastrointestinal Lesions

Abstract: Superficial neoplastic lesions of the digestive tract are usually asymptomatic, and often represent incidental findings on endoscopy. The Paris Classification was developed for the systematic evaluation of superficial lesions of the oesophagus, stomach and colon. The significance of this classification in clinical practice is that it allows the depth of invasion to be estimated. Chromoendoscopy is used to improve the visualization of gastrointestinal lesions. There are 2 types of chromoendoscopy: dye and virtu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…According to the Paris classification, colonic neoplastic lesions stratify into polypoid (pedunculated 0-Ip, sessile 0-Is and semi-pedunculated 0-Isp), non-polypoid (elevated 0-IIa, flat 0-IIb, depressed 0-IIc), and excavated or ulcerated lesions (0-III). 7 IIc and 0-III are depressions less than 1.2 mm and greater 1.2 mm, respectively 8 Utilizing the Paris classification in common practice provides an estimation for depth of invasion. According to the original Paris workshop, of the 3680 colonic lesions, the proportion of invasion into the submucosa was 5% for 0-Ip, 34% for 0-Is, 4% for 0-IIa, 0% for 0-IIb, and 61% for 0-IIc lesions.…”
Section: Indications Of Esd For Colonic Lesionsmentioning
confidence: 99%
“…According to the Paris classification, colonic neoplastic lesions stratify into polypoid (pedunculated 0-Ip, sessile 0-Is and semi-pedunculated 0-Isp), non-polypoid (elevated 0-IIa, flat 0-IIb, depressed 0-IIc), and excavated or ulcerated lesions (0-III). 7 IIc and 0-III are depressions less than 1.2 mm and greater 1.2 mm, respectively 8 Utilizing the Paris classification in common practice provides an estimation for depth of invasion. According to the original Paris workshop, of the 3680 colonic lesions, the proportion of invasion into the submucosa was 5% for 0-Ip, 34% for 0-Is, 4% for 0-IIa, 0% for 0-IIb, and 61% for 0-IIc lesions.…”
Section: Indications Of Esd For Colonic Lesionsmentioning
confidence: 99%
“…Previous studies have shown that the use of the Paris classification during white light endoscopic examination in the detection of EGC has yielded a sensitivity and specificity of 71.2% and 99.1%, respectively [ 11 , 12 ]. Another study showed that the overall accuracy for predicting the invasion depth of EGC based on this classification was 78.0% [ 13 ].…”
Section: White Light Endoscopy and Macroscopic Assessmentmentioning
confidence: 99%
“…3,4 Clinically, early gastrointestinal cancer is classified as early esophageal cancer, early colorectal cancer, and early gastric cancer, depending on the site of the lesion. 5,6 Early screening and diagnosis of gastrointestinal cancer are essential for improving prognosis. Previous studies have revealed a low level of knowledge and awareness regarding screening for early gastrointestinal cancer in China, especially in ethnic minority areas, posing a barrier to early diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%